Efficacy and safety of the Calistar and Elevate anterior vaginal mesh procedures. (August 2019) - Rogowski, Artur; Kluz, Tomasz; Szafarowska, Monika; Mierzejewski, Pawel; Sienkiewicz-Jarosz, Halina; Samochowiec, Jerzy; Bienkowski, Przemyslaw; Baranowski, Wlodzimierz
Abstract: Objectives: The pelvic organ prolapse (POP) surgery with implantation of anterior transvaginal mesh (e.g. Elevate or Calistar) may provide objective and subjective improvement as compared to traditional POP repair without mesh. Given differences between the Elevate and the Calistar mesh and their different placement methods, some variation inlong-term clinical outcomes of these anterior vaginal mesh procedures can be expected. Study design: The purpose of the study was to compare the 18-month operative success in patients who had undergone anterior POP surgery with either the Calistar (n = 54) or Elevate mesh (n = 50). Results: There were no between-group differences in objective measures of operative efficacy, including POP-Q anterior stage 0 or I (94% for Calistar, 92% for Elevate) and "no descent beyond the hymen" (98% for Calistar, 94% for Elevate). The proportion of patients with subjective measure of operative efficacy (no vaginal bulge symptoms) did not differ between the groups (91% for Calistar, 78% for Elevate). There were no between-group differences in the proportion of women suffering from vaginal exposure, de novo stress urinary incontinence (SUI), de novo overactive bladder (OAB) symptoms, pelvic floor pain or dyspareunia. The operative cure of OAB symptoms was similar in the groups. The proportion of patients with the operative cure of SUI symptoms was significantly higher in the Calistar as compared to the Elevate group. Conclusions: The results suggestthat the Calistar system offers similar efficacy in the treatment of anterior and both anterior and apical POP as compared to the Elevate. The use of anterior Calistar is associated with some additional benefits, i.e. SUI treatment in patients with concomitant anterior and both anterior and apical POP and SUI symptoms.